Energy Poverty and Vulnerability A Global Perspective - Thomson, Harriet; Petrova, Saska; Bouzarovski, Stefan; Simcock, Neil (Taylor & Francis, 2018)
Human health and well being are closely intertwined with the ability to access affordable and modern domestic energy services, including heating, cooling, lighting, cooking, and information technology. Energy poverty is said to occur when such amenities cannot be secured up to a socially- and physically- necessitated level. Millions of people across the world suffer from energy poverty due to a combination of financial, social and technical circumstances. Energy Poverty and Vulnerability provides novel and critical perspectives on the drivers and consequences of energy-related injustices in the home. Drawing together original research conducted by leading experts, the book offers fresh and innovative insights into the ways in which hitherto unexplored factors such as cultural norms, environmental conditions and household needs combine to shape vulnerability to energy poverty. Case studies from a wide range of countries are presented, thus providing the first globally-integrated account of a policy and research domain that has previously been divided between the Global South and North. An examination of the diverse manifestations of energy poverty is supplemented by an identification of this condition's shared and context-specific causes. Conveying policy-relevant insights that can inform decision-making, this book can be of great interest to students and scholars of energy demand, social justice, and sustainability transitions, as well as decision-makers and practitioners who wish to find out more about this complex issue.